Perancangan Aplikasi Interaktif Berbasis Augmented Reality AR Dengan Tema Dinosaurus Untuk Anak Usia Dini - Prasetya, Bima; Rahmawati, Anik (Fakultas Komputer Dan Desain, 2025)
The advancement of digital technologi has led to the emergence of interactive learning media. One such innovation is Dinoland, an educational application utilizing augmented reality (AR) designed to introduce and foster children’s interest in dinosaurus and othe prehistoric subjects. The development process follows the glass box design methode, which includes four key stages: preparation, incubation, illumination and verification. Dinoland presents engaging educational content through 3D visual, child-friendly charcter, and interactive features that encourage user participation. Additionally, the application is supported by complementary tools such as puzzles, flashcards and educational calender. With these feature, Dinoland aims to be an effective and innovative learning medium that can be widely accessed through digital platforms like the google play store